STRATEGI PENEGAKKAN HUKUM MENINGKATKAN KINERJA ORGANISASI KORLANTAS POLRI - Cornelis Ferdinan Hotman Sirait,; Zulkifli, Zulkifli; Agustinus Miranda W, (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2023)
The purpose of this study was to Strategy the Law Enforcement strategy for Organizational Performance at the Korlantas Polri institution, This research uses qualitative research methods. Qualitative analysis using SWOT, IFE & EFE and QSPM. The results of strategy analysis research through the input strategy stage with IFE, EFE, &CPM matching stage with TOWS and decision stage with the strategy used from the QSPM results are alternative strategy of Digital Leadership transformation & Adaptiv. The Implication : Strategic planning is carried out using the principle of strategic agility and adjusting the organizational structure of the National Police Traffic Corps in an agile and adaptive system